2013
DOI: 10.1016/s2221-1691(13)60185-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of quorum sensing in Chromobacterium violaceum by Syzygium cumini L. and Pimenta dioica L.

Abstract: Asian Pac J Trop Biomed 2013; 3(12): 954-959

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 25 publications
1
25
2
Order By: Relevance
“…Another study by Huber et al (2003) showed anti quorum sensing effects of isolated phenolic compounds such as epigallocatechin gallate (EGCG), gallic acid and tannic acid on the bioluminescence of the quorum sensing biosensor E. coli MT102 pSB403 and the fluorescence of Pseudomonas putida pKR-C12, as well as biofilm formation and swarming motility in Burkholderia cepacia. In another study, the production of violacein was completely abolished by leaves of Centella asiatica L. and Adenanthera pavonina L, and the role of flavonoids on this action was suggested (Vasavi et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another study by Huber et al (2003) showed anti quorum sensing effects of isolated phenolic compounds such as epigallocatechin gallate (EGCG), gallic acid and tannic acid on the bioluminescence of the quorum sensing biosensor E. coli MT102 pSB403 and the fluorescence of Pseudomonas putida pKR-C12, as well as biofilm formation and swarming motility in Burkholderia cepacia. In another study, the production of violacein was completely abolished by leaves of Centella asiatica L. and Adenanthera pavonina L, and the role of flavonoids on this action was suggested (Vasavi et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the above mentioned studies, medicinal plants have also been searched for quorum sensing inhibition against violacein production for extracts of Syzygiumcumini L. and Pimenta dioica L (Vasavi et al, 2013) and bioluminescence inhibition in V. harveyi for extracts from Rhizophora annamalayanacasca (Musthafa et al, 2013). Seeds from Cuminum cyminum, popularly known as cumin, presented as potent inhibitors of quorum sensing in C. violaceum, with inhibition reaching 86% with no measurable interference on bacterial growth (Packiavathy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study, Shukla and Bhathena (2014) [ 50 ] have reported that several tannin-rich crude extracts show a broad spectrum of anti-QS activity. Another qualitative study on anti-AHL activity of pericarp of Punica granatum and an ethyl acetate fraction of S. cumini leaves has also been reported [ 22 , 51 ]. Hasan et al (2012) [ 23 ] have reported that P. emblica fruit extract can suppress quorum sensing genes in S. mutans .…”
Section: Resultsmentioning
confidence: 99%
“…Crude extracts of many plant parts were shown to possess anti-QS activity using C. violaceum as a model bacterium [19], [20], [21]. Crude plant extracts are often found to be more effective than isolated constituents at an equivalent dose perhaps owing to positive interactions between components of whole plant extracts.…”
Section: Introductionmentioning
confidence: 99%